THE EFFECT OF THE FINGERPRINT METHOD ONTHE ABOUT CALCULATION OF CLASS III - Latifatu Sadiah, Tia; Maria Dewi, Sinta; Dwi Lestari, Lutfi; Kohar Mudzakar, Mochamad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of the JARIMATIKA method on the ability to calculate multiplication of class III in Mathematics subject at SDN Karawang Wetan V, East Karawang District. This research is a quantitative type of research. The population used in this study were all grade III students of SDN Karawang Wetan V, East Karawang District, amounting to 74 students. A sample of 50 students from population members was taken from 25 students in the experimental class and 25 students in the control class. Data collection techniques in this study through the ability to count multiplication in Mathematics. The instrument in this study was in the form of a short test item. The data analysis technique used was statistical calculations. Theresults of the validity test about the students’ ability to count multiplication in mathematics obtained 10 instruments which were declared valid from the 10 items tested. The results of the reliability test obtained an rxy value of 0.890. Hypothesis calculation using the ttest namely Independent sample T test and obtained at a significant level of 0.05 indicates that the probability value (significance) is 0.000. Because the significance value of 0.000 <α = 0.05, with the conference to the results of t arithmetic> t table (6.902> 1.675) then Ho is rejected. This proves that there is an influence of the use of the JARIMATIKA method on the ability to calculate multiplication in third grade students in the even semester of SDN Karawang Wetan V